Addictive internet behaviors: The role of trait emotional intelligence, self‐esteem, age, and gender. Issue 3 (5th December 2020) - Sechi, Cristina; Loi, Giorgia; Cabras, Cristina
Abstract : Internet is essential part of everyday life and certainly facilitate it on several levels. It is a helpful information tool, and knowledge, but its unlimited range often is risky for users. The behaviors and outcomes of internet abuse have already been well‐documented in the literature; less is known about the role of personal factors that reinforce internet addiction. Based on the Interaction of Person‐Affect‐Cognition‐Execution model (I‐PACE), the current study investigates the role of trait emotional intelligence and self‐esteem, age, and gender in relation to addictive internet behaviors. We conducted an online investigation among respondents. The participants were Italian university students who voluntarily completed the Abuse Internet Addiction scale (UADI) and the Rosenberg Self‐esteem scale. Path analysis results revealed that both trait emotional intelligence and self‐esteem had a protective direct effect on addictive internet behaviors. Age negatively affects addictive internet behaviors; younger are more likely to develop addictive internet behaviors than older individuals. Finally, we did not find an effect of gender on addictive internet behaviors. Our results suggest the need to develop prevention plans for addictive internet behaviors and educational programs to increase emotional intelligence and self‐esteem components to help younger to improve interpersonal and emotional management skills to better handle their internet use.